Tertullian, on idolatry and Mishnah ʹAvodah zarah : questioning the parting of the ways between Christians and Jews in late antiquity - Binder, Stephanie E. (Jewish and Christian Perspectives Series, 2012)
This work studies and compares systematically the text of Tertullian, an African Church Father of the third century CE, on idolatry with the rabbinic Mishnah Avodah Zarah , on the same subject, dating roughly from the same period. Similarities and differences between the Jewish and Christian approaches to idolatry are examined and accounted for. The research is inscribed in the wider framework of discussions on the "parting of the ways" between Jews and Christians. It also addresses related questions such as the role of the rabbis in second and third century Judaism in the Land of Israel and in the Diaspora; relations between Jews living in those places; interactions between Jews and pagans, Christians and pagans, Jews and Christians...